2016
DOI: 10.1016/j.jtcvs.2015.10.114
|View full text |Cite
|
Sign up to set email alerts
|

Delirium after surgical and transcatheter aortic valve replacement is associated with increased mortality

Abstract: Objective The purpose of this study was to determine the incidence and clinical significance of postoperative delirium (PD) in patients with aortic stenosis undergoing surgical aortic valve replacement (SAVR) or transcatheter aortic valve replacement (TAVR). Method Between 2010 and 2013, 427 patients underwent TAVR (n = 168) or SAVR (n = 259) and were screened for PD using the Confusion Assessment Method for the Intensive Care Unit. The incidence of PD in both treatment groups was determined and its associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
81
2
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 24 publications
12
81
2
3
Order By: Relevance
“…Several hypotheses have been postulated, including neurotransmitter imbalances, inflammatory processes, and physiologic stress. Advanced age and multiple comorbidities are also known risk factors for development of delirium, although we could not find associations between incidence of IHPOD after TAVR and mean age, percentage of participants treated with non‐TF access, and logistic EuroSCORE. Our metaregression was performed at the study level, with lack of participant‐level data; thus, considering the mean values of tested variables (and not individual data) from included studies; such limitations may have reduced the power of our metaregression to find similar associations.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Several hypotheses have been postulated, including neurotransmitter imbalances, inflammatory processes, and physiologic stress. Advanced age and multiple comorbidities are also known risk factors for development of delirium, although we could not find associations between incidence of IHPOD after TAVR and mean age, percentage of participants treated with non‐TF access, and logistic EuroSCORE. Our metaregression was performed at the study level, with lack of participant‐level data; thus, considering the mean values of tested variables (and not individual data) from included studies; such limitations may have reduced the power of our metaregression to find similar associations.…”
Section: Discussioncontrasting
confidence: 69%
“…The majority of participants included in our meta‐analysis were derived from 2 large prospective registries, with the lack of information regarding delirium diagnostic criteria and timing of the delirium screening . Interestingly, while these 2 large studies reported lower incidence of IHPOD after TAVR (e.g., 3.8% and 4.6%), small studies included in our analysis report higher incidence of IHPOD after TAVR . Several participant‐ and procedural‐related factors, including age at admission, comorbid condition, TAVR access, and hospital complication rate, could explain the differences in the incidence of IHPOD between these studies.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Incidence peaks of kidney, urinary bladder and prostate cancers were around 60-80 years of age. Because the development of delirium in surgical patients has been associated with negative outcomes including a higher risk of postoperative mortality, [2,7,8] geriatric assessment in older patients with genitourinary cancers, and management of postoperative delirium is an important issue. [9] However, only few studies included very few patients have evaluated postoperative delirium incidences after urological surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In patients over 65 years of age undergoing cardiac surgery, postoperative delirium has a reported incidence of 26 to 52%. The estimated incremental cost of PD after cardiac surgery is 150 billion dollars annually in the United States . TAVR patients had 29% incidence of PD in the best study to date .…”
mentioning
confidence: 99%